NCMP-14. EEG FEATURES THAT INDEPENDENTLY ASSOCIATE WITH HIGHER GRADE NEUROTOXICITY IN PATIENTS TREATED WITH CHIMERIC ANTIGEN RECEPTOR (CAR) T CELL THERAPY. (11th November 2019) - Mao, David; Kotchetkov, Ivan; Reiner, Anne; Panageas, Katherine; Chen, Xi; Avila, Edward; Santomasso, Bianca
Abstract: RATIONALE: CAR T cell therapy has emerged as a promising treatment of refractory or relapsed leukemia and lymphoma. It is associated with severe side effects, such as immune effector cell-associated neurotoxicity syndrome (ICANS). Electroencephalography (EEG) is often performed in these patients as part of an evaluation of their altered mental status. We hypothesize certain EEG features are associated with high ICANS grade. METHODS: Retrospective review of medical records was performed. From February 2010 through June 2016, 53 adults with relapsed B-cell acute lymphoblastic leukemia received 19-28z CAR T cells at MSKCC as part of a phase 1 trial. We identified patients from this group who were monitored with video EEG and recorded daily EEG features. A multivariable generalized estimating equation model was used to identify EEG findings that were independently associated with high ICANS grade (3 or 4). A Cox model was used to associate initial EEG findings with development of high ICANS grade. RESULTS: There were 27 unique patients with a combined 109 days of video EEGs. In a multivariable model, lack of posterior dominant rhythm (PDR) (Odds Ratio (OR)=12.49, p< .0001) and discontinuity (OR=9.50, p=0.01) were independently statistically significantly associated with high ICANS grade and generalized sharps retained marginal statistical significance (OR=4.77, p=0.06). Presence of state changes, focal slowing, generalized slowing, and epileptic discharges did not have statistically significant association. No EEG findings on initial day of monitoring was statistically significantly associated with eventual development of high ICANS grade. CONCLUSIONS: EEG discontinuity and lack of PDR were associated with high severity of neurotoxicity. There may be clinical utility in monitoring for specific features when assessing for development or resolution of ICANS, but additional prospective studies employing EEG in patients receiving CAR T cell therapy are necessary.